Religious Strengthening Program to Improve Student Discipline at SMPN 2 Pandaan in 2024 - Masruroh, Lilik (Civiliza Publishing, Indonesia., 2024)
Education is a planned effort, in creating a learning atmosphere and learning process, so that students actively develop their potential, to have spiritual religious strength, self-control, personality, intelligence, noble morals and necessary skills. The purpose of this study is to examine how the implementation of the religious strengthening program in improving student discipline at SMP Negeri 2 Pandaan. In this study, the author used a qualitative method, namely a research procedure that produces and Descriptive in the form of written or oral data from people and observable behavior. The results of the study indicate that the religious strengthening program has the aim of improving the Understanding of Religious Teachings, building moral and ethical character, and strengthening social ties within the community. From the reality at SMPN 2 Pandaan that this school has proven by improving student behavior towards discipline.